Strategies to enhance entrepreneurship education at the University of Venda - Livhuwani Gladys Nkondo; Zanele Mashimbye; Vhuthu Mampheu (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2026)
This study explores the strategies to enhance entrepreneurship education at the University of Venda in South Africa, with the aim of promoting student entrepreneurship and contribute to economic growth and job creation. The research adopted a qualitative research approach; phenomenological design grounded in the constructivist paradigm to gain in-depth insights of students’ experiences in entrepreneurship education. The targeted population comprised University of Venda student-entrepreneurs who participate in entrepreneurship education programmes, and those who are registered for entrepreneurship courses. A convenience sampling technique was used to select 10 students and data was collected through semi-structured face-to-face and telephone interviews according to the research objectives. The collected data was analysed thematically using Atlas.ti version 8.4. the study findings revealed that while entrepreneurship education is present at the university, its effectiveness is hindered by limited practical experience, insufficient institutional support, and outdared curriculum, among other things. The recommendations made include the suggestion that the University of Venda should collaborate with private companies and government to create internship opportunities for entrepreneurship students to gain hands-on experience. This study is among the first to have managed to identify the strategies to enhance entrepreneurship education. This study was conducted at the University of Venda which means the results may not be generalised in other universities. The researcher, however, further recommends that similar studies can be conducted in other universities to find out any similarities or differences in the conclusions, thereby enlarging the literature on the topic.